Monitoring manual dexterity in dental students — a quasi-longitudinal study and insights from a natural pandemic experiment - Zarzecka-Francica, Elżbieta; Gala, Andrzej; Myciński, Paweł; Pihut, Małgorzata (Folia Medica Cracoviensia, 2026)
Clinical classes for dental students in Poland start at the beginning of the third year and continue until the end of the fifth year. The implementation of theoretical knowledge tests and trains their manual skills and makes visible the complexity and variability of clinical cases. The COVID-19 pandemic forced a clinical lockdown, interrupting students’ ability to train for six months. The aim of the study was to compare manual dexterity scores measured by the Purdue Pegboard Test (PPT) before and after clinical lockdown among third- and fifth-year dental students and to assess the role of clinical placement. We investigated whether the initial female manual dexterity advantage has changed and whether the subjective assessment of dexterity correlates with objective measurement. The study consisted of students performing PPT subtests, tallying the score and answering additional questions. The cross-sectional (quasi-longitudinal) study included 175 students; 96 before the outbreak of the pandemic and 79 who took a six-month break from full-time classes. Measurements were taken each time for Year III at the very beginning of the start of practical classes, and for Year V at the end. Analysis comparing cohorts studied before and after the clinical lockdown revealed no significant differences in PPT scores within the same year of study. However, fifth-year students achieved higher scores than thirdyear students on selected PPT subtest. The t-Welch test showed that year V scores significantly higher on most subtests compared to year III. In a two-factor ANOVA analysis, women scored higher than men on all subtests. Spearman’s correlation analysis revealed a lack of correlation between self-esteem and objective PPT scores among third- and fifth-year students. The findings may suggest a relative stability of the assessed aspects of manual dexterity during a break lasting up to six months, and clinical seniority was associated with higher PPT score. The gender effect persisted, while self-assessment did not coincide with objective measurement supporting the need for objective monitoring of teaching needs.